PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT TIRTA JAYA PERKASA JAKARTA DIVISI KEAMANAN - Nandyansyah; Safi’I, Mohamad (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to find out how much influence Compensation and Work Motivation has on Employee Performance at the Division of PT. Tirta Jaya Perkasa, either partially or simultaneously. This research method uses quantitative methods with a descriptive approach. The sampling technique in this study used a saturated sample of 58 respondents. The analysis technique used is validity test, reliability test, classical assumption test, normality test, multicollinearity test, heteroscedasticity test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient test, coefficient of determination test and hypothesis test. The results of this study are testing the hypothesis partially on the Compensation variable (X1) obtained by tcount > ttable (8,088 > 1,673) and a significance value of 0.000 <0.05. This means that Compensation Style (X1) has a significant effect on Employee Performance (Y). Partially testing the hypothesis of the Work Motivation variable (X2) obtained tcount > ttable (7.970 > 1,673) and a significance value of 0.000 <0.05. This means that Work Motivation (X2) has a significant effect on Employee Performance (Y). Simultaneous hypothesis testing obtained fcount > ftable (45,908 > 3,165) and a significance value of 0.000 <0.05. So it can be concluded that Leadership Style (X1) and Communication (X2) have a significant simultaneous effect on Employee Performance (Y). The determination obtained by Rsquare is 0.852, meaning that the variables of Compensation and Work Motivation together have an influence contribution of 62,5% on employee performance. While the remaining 37,5% is influenced by other factors that were not examined in this study.